In-situ measurement of machining part deflection with Digital Image Correlation. (January 2022) - Rebergue, G.; Blaysat, B.; Chanal, H.; Duc, E.
Abstract: In the context of the aeronautics industry, aluminum alloy structural parts are manufactured in several stages, from forming processes and heat treatments to final machining. Some process steps may generate residual stresses. Thus, material removal during machining releases these residual stresses, which induces part deformation. Such deformations can lead to geometric nonconformity of the machined part. It is therefore essential to control this phenomenon. Due to the variability in residual stress distribution in each raw part, the modeling approaches must to be coupled with experimental measurements. This article thus aims to define a reliable experimental technique for measuring in-plane deformation of large aeronautical parts during their machining. The backbone of the technique relies on Digital Image Correlation (DIC), which enables the contactless measurement of part deformation during machining. Moreover, DIC provides a full-field measurement and a direct evaluation of part deformations. This work discusses more specifically problems related to the use of DIC during machining, the latter corresponding to a particularly harsh environment. Indeed, optical systems undergo undesirable movement and metal chips hide areas of the observed part. These unwanted events corrupt the results. In order to control these problems and consistently apply DIC part deformation measurement during machining, specific methods are proposed in this paper. Finally, DIC measurements are performed during the same machining sequence of two parts. The excellent agreement of the two measurements confirms the reliability of the technique. Finally, measurements are discussed, emphasizing the contribution they provide to the machining community. Graphical abstract: Highlights: Digital Image Correlation (DIC) is implemented in a Machining Tool workspace. DIC compensation methods are introduced to circumvent the harsh machining context. The measurement technique is validated thanks to an uncertainty study. DIC measurements are in agreement with an offline conventional probing machine. DIC measurement is possible during machining.